Jinx - Blackwood, Sage. (New York : Harper, 2013)
A young boy named Jinx encounters magic and danger as he grows up in the deep, dark forest known as the Urwald and discovers that the world beyond--and within--the Urwald is more complex than he could imagine.
School Library Journal starred, January 2013.
Pub Weekly, November 2012.
Kirkus Starred, November 2012.
School Library Journal starred.
Pub Weekly.
Kirkus Starred.
Keywords: Magic -- Juvenile fiction; Magic -- Fiction; Fantasy; Magic -- Fiction; Fantasy fiction; Magic -- Fiction; Wizards -- Fiction; Orphans -- Fiction; Forests and forestry -- Fiction; Fantasy; Fantasy fiction